PENGARUH KOMPENSASI, KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Karyawan PTP. Nusantara IX (Persero) - Mikanisme Finalis, 10.05.51.0117; Yunianto, Askar (Students Journal of Economic and Management, 2014)
This study aimed to analyze the effect of compensation, organizational commitment and job satisfaction on employee performance PTP. Nusantara IX (Persero). Data used in this study is primary data is data obtained directly from the original source. While the techniques used for data collection using questionnaire by asking a number of written questions used to obtain information and respondents. The populations in this study were all employees of PTP. Nusantara IX (Persero), amounting to 152 people. Based on purposive sampling, then obtained a sample of 105 people. Test equipment in this study using a test the validity of using factor analysis, reliability testing using Cronbach Alpha and hypothesis testing using multiple linear regressions. The results of the analysis can be concluded that: (1) Compensation has positive influence on employee performance. The higher the compensation received, and then the employees performance will be increased. (2) Organizational commitment has a positive effect on employee performance. The better application of organizational commitment, then the employees performance will be increased. (3). Job satisfaction has a positive effect on employee performance. The higher the job satisfaction, the employeeâs performance will be increased.Keywords : Compensation, Organizational Commitment, Job Satisfaction And Employee Performance